Developmental topographical disorientation: Case one - Iaria, Giuseppe; Bogod, Nicholas; Fox, Christopher J.; Barton, Jason J.S. (Neuropsychologia, 2009)
Topographical disorientation is the inability to orient within the environment, usually acquired from lesions to different cerebral regions participating in the attentional, perceptual or memory functions involved during navigation. We present the first case of a patient with topographical disorientation in the absence of any structural lesion and with intact sensory and intellectual function. Experimental tests in both real and virtual environments revealed a selective impairment in forming a mental representation of the environment, namely a cognitive map. Consistent with the patient's behavioural findings, a functional magnetic resonance imaging (fMRI) study showed lack of activation in the hippocampal complex and the retrosplenial cortex while forming a cognitive map of the environment. Although the lack of neural activity results in a negative finding that generally has low interpretative value, in this specific case our findings may provide useful information. First, in a group of healthy control subjects performing the same task, activity within the hippocampal complex and retrosplenial cortex were detected in each individual participant. Second, we found that within the same regions (showing lack of neural activity while forming a cognitive map of the environment) increased neural activity was detected while the patient was performing a different navigation task. This case is the first evidence reported in the literature showing that topographical disorientation may occur as a developmental defect causing a lifelong disorder affecting daily activities.